Impact of drifts on divertor power exhaust in DIII-D. (May 2019) - Jaervinen, A.E.; Allen, S.L.; Eldon, D.; Fenstermacher, M.E.; Groth, M.; Hill, D.N.; Lasnier, C.J.; Leonard, A.W.; McLean, A.G.; Porter, G.D.; Rognlien, T.D.; Samuell, C.M.; et al.
Highlights: Strong impact of drifts on low field side detachment in DIII-D H-modes. Step-like onset of strong detachment in fwd. BT also observed in UEDGE simulations. Shallow detachment state in rev. BT also observed in UEDGE simulations. Similar impact of drifts on detachment in experiments with N2-injection. Abstract: Radiative divertor experiments and 2D fluid simulations show strong impact of cross-field drifts on the low field side (LFS) divertor target heat flux and volumetric radiation profiles when evolving to detached conditions in DIII-D high confinement mode (H-mode) plasmas with forward and reversed toroidal field configurations. In both field configurations, the peak heat flux is reduced by about a factor of 2 in detachment by D2 -injection and by factor of 3 – 4 in detachment by N2 -injection. Operating with the B × ∇B-drift towards the X-point (fwd. B T ), the LFS divertor radiation front is observed to shift step-like from the target to near to the X-point at the onset of detachment. In contrast, operating with the B × ∇B-drift away from the X-point (rev. B T ), the radiation front is observed to remain closer to the target plate and to be radially shifted towards the far SOL. These phenomena occur with detachment induced both with N2 - and D2 -injection. The step-like detachment onset is consistent with recently published theory of the role of poloidal E × B -drift in the private flux region in driving highly non-linear detachment onset in fwd. B T [22].